PERANCANGAN 3D VIDEO GAME AKSI BERCORAK BUDAYA INDONESIA DENGAN PENDEKATAN UI/UX - Hadi, Farhan Hidayatul; Nadya, Nadya (Universitas Bunda Mulia, 2024)
The rapid growth of technology and the gaming industry in Indonesia, along with the increasing number of gamers, presents a significant opportunity to promote local culture. As Indonesia ranks third in the world for the number of gamers, a major challenge is the inadequate representation of local culture, often skewed towards international markets. Local game developers face barriers such as a lack of formal education and difficulties in creating culturally accurate content, despite efforts by the government and studios to enhance cultural representation. This study employs a qualitative-descriptive approach, utilizing data collection methods including interviews, observations, document studies, literature reviews, and questionnaires. The design methodology used is the Multimedia Development Life Cycle, focusing on creating a UI/UX that reflects Javanese culture and employing low poly 3D modeling to ensure accessibility and an engaging visual experience. The game titled